The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5946/ce.2018.041
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Changes in the Small Intestines in Portal Hypertension: First Study Using the Pillcam SB3 Capsule Endoscopy System

Abstract: Background/AimsTo evaluate patients with portal hypertension (PH) of varied etiologies for portal hypertensive enteropathy (PHE) using the PillCam SB3 capsule endoscopy (CE) system. MethodsConsecutive patients with PH presenting with unexplained anemia and/or occult gastrointestinal bleeding were evaluated using the PillCam SB3 CE system. Abnormal findings were categorized as vascular or non-vascular. The patients with ongoing bleeding caused by PHE were treated. The correlation of the CE scores of PHE with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It is being increasingly diagnosed, due to the advent of video capsule endoscopy and deep enteroscopy. In recent studies, the prevalence of PHE varies around 93-97%, with 8-12% of patients showing evidence of ongoing bleeding [62][63][64]. The findings of PHE are characterized as vascular (red spots, telangiectasia, or varices) and non-vascular or inflammatory (villous edema, erythema, or polyps) changes [64] (Figure 12a-f).…”
Section: Portal Hypertensive Enteropathy (Phe)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is being increasingly diagnosed, due to the advent of video capsule endoscopy and deep enteroscopy. In recent studies, the prevalence of PHE varies around 93-97%, with 8-12% of patients showing evidence of ongoing bleeding [62][63][64]. The findings of PHE are characterized as vascular (red spots, telangiectasia, or varices) and non-vascular or inflammatory (villous edema, erythema, or polyps) changes [64] (Figure 12a-f).…”
Section: Portal Hypertensive Enteropathy (Phe)mentioning
confidence: 99%
“…Treatment options for PHE related bleed include glue or sclerosant for variceal bleeding and APC for non-variceal bleeding. In patients with hemodynamic instability, radiological coil embolization is an option [64].…”
Section: Portal Hypertensive Enteropathy (Phe)mentioning
confidence: 99%
“…In fact, OGIB is the most common indication for CE in patients with cirrhosis [ 13 ]. Furthermore, although the bleeding potential of mucosal red spots is uncertain, they are frequently found during CE for investigation of unexplained iron deficiency anemia and can occur as manifestations of several conditions, including portal hypertensive enteropathy and systemic vasculitis [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies that compared SB2 and SB3 reported that SB3 shows a significantly reduced reading time and a significantly improved detection rate, while other studies have reported no significant differences between SB2 and SB3 [21,23-27]. In addition, some of the polyps classified as PHE in the study by Goenka et al [22] may be tumorous lesions such as adenomas, and not inflammatory changes. Thus, further studies are needed to analyze whether PHE detection is indeed increased with the use of SB3.…”
mentioning
confidence: 97%
“…In this issue of Clinical Endoscopy , Goenka et al [22] evaluated the small bowels of patients with PH of various etiologies who had symptoms of unexplained anemia or occult GI bleeding, using the PillCam SB3 CE system, focusing on PHE. Abnormal findings were categorized into vascular (red spots, telangiectasia, or varices) and non-vascular/inflammatory lesions (villous edema, erythema, or polyps).…”
mentioning
confidence: 99%